Pengaruh Faktor-Faktor Individual Terhadap Perilaku Etis Auditor Pada Inspektorat Provinsi Gorontalo - Abdul, Yusrin; Sondakh, Jullie J; Tinangon, Jantje (Universitas Sam Ratulangi, 2019)
Abstract. This study aims to know and analyze the effects of individual factors namely internal locus of control, intellectual intelligence, emotional intelligence, and spiritual intelligence on the ethical behavior of the Gorontalo Provincial Inspectorate auditors. This is a quantitative research. The population in this study was all staff of the Gorontalo Provincial Inspectorate. Samples are auditors having certification of the Auditor's Functional Position (JFA). This study included 44 respondents. Data were collected by questionnaires. Data were analysed by multiple regression and SPSS program. The results of the study showed that an internal locus of control affects increasing auditor ethical behavior. Intellectual intelligence (IQ) increases auditor ethical behavior. Emotional Intelligence (EQ) increases auditor ethical behavior. Spiritual Intelligence (SQ) does not increase the auditor's ethical behavior.Keywords: Internal Locus of Control, Intellectual Intelligence, Emotional Intelligence and Spiritual Intelligence on the Ethical BehaviorAbstrak. Penelitian ini bertujuan untuk mengatahui dan menganalisis pengaruh faktor-faktor individual yakni locus of control internal, kecerdasan intelektual, kecerdasan emosional dan kecerdasan spiritual terhadap perilaku etis auditor Inspektorat Provinsi Gorontalo. Jenis penelitian ini adalah penelitian kuantitatif. Populasi dalam penelitian ini adalah seluruh pegawai Inspektorat Provinsi Gorontalo dengan sampel penelitian yakni auditor memiliki sertifikasi Jabatan Fungsional Auditor (JFA) yang berjumlah 44 responden. Metode pengumpulan data menggunakan kuesioner dengan menggunakan analisis data regresi berganda dengan bantuan SPSS. Hasil penelitian menunjukkan Locus of Control Internal berpengaruh dalam meningkatkan perilaku etis auditor. Kecerdasan Intelektual (IQ) berpengaruh dalam meningkatkan perilaku etis auditor. Kecerdasan Emosional (EQ) berpengaruh dalam meningkatkan perilaku etis auditor. Kecerdasan Spiritual (SQ) tidak berpengaruh dalam meningkatkan perilaku etis auditor.Kata kunci : Locus of Control Internal, Kecerdasan Intelektual, Kecerdasan Emosional, Kecerdasan Spiritual, Perilaku Etis